The role of basic psychological needs satisfaction in the relationship between transformational leadership and innovative work behavior - Gerhard Messmann; Arnoud Evers; Karel Kreijns (Human Resource Development Quarterly, 2021)
The aim of this contribution was to investigate predictors of innovative work behavior (IWB) in nonprofit organizations. For instance, in schools, innovative solutions are crucial as the quality of education and therefore the schools' competitiveness depends on their ability to keep pace with technological, economic, and societal transformations. We addressed this issue in a quantitative study with 130 teachers in Dutch secondary schools employing a time-lag design. In accordance with self-determination theory, we investigated the role of transformational leadership for enhancing IWB and the role of basic psychological needs satisfaction in mediating this relationship. By employing structural equation modeling, we found that transformational leadership was positively related to the satisfaction of the teachers' needs for autonomy and competence. Furthermore, the satisfaction of the need for competence positively predicted teachers' IWB. In addition, perceived competence fully mediated the relationship between transformational leadership and teachers' IWB. Accordingly, persons with leadership responsibilities should adopt a transformational leadership style and motivate their employees by providing individual attention, intellectual stimulation, and encouragement for goal striving. Specifically, leaders may provide feedback on employees' innovative ideas and their strategies for realizing innovative solutions, thus helping them to become increasingly confident about what they can achieve and improve concerning their contributions to innovation development. For human resource development (HRD) professionals, our findings imply that efforts toward leadership training and development (e.g., training, coaching, and mentoring) should incorporate knowledge and practical experiences about transformational leadership as well as its role for employees' IWB and their contributions to organizational and professional development.
Keywords: 650; basic psychological needs satisfaction; innovative work behavior; time-lag design; transformational leadership